Experimental investigation on modelling and prediction of optimal process parameters for the wear behaviour of hybrid polymer matrix composite - K. Karthik; K. Elavarasan; Beemkumar Nagappan; Subhaprada Dash; Krishna Kumar Shukla; Arpit Arora; Venkata Ramesh Reddy V; Kamakshi Priya Kumar (Results in Engineering, 2025)
This study presents the development and characterization of hybrid polymer matrix composites (HPMCs) engineered to enhance wear resistance for structural and industrial applications. Composites were fabricated using a vacuum bag molding technique, incorporating Kevlar fibers, carbon fibers, and ceramic nanoparticles within an epoxy matrix to ensure uniform fiber distribution and effective interfacial bonding. Tribological testing demonstrated that the addition of ceramic nanoparticles reduced the wear rate by 35 % compared to the unmodified composite. The optimal wear performance was achieved under a load of 45 N, a sliding velocity of 900 m/s, and a sliding distance of 15 m. An increase in laminate thickness correlated with improved wear resistance, and the carbon fiber content was identified as a key factor influencing overall composite performance. The study also established quantitative relationships between fiber composition, applied load, and sliding conditions. This work introduces a novel vacuum bag molding process tailored for multi-fiber HPMCs and proposes application-specific composite formulations suitable for use in boat hulls, automotive components, and structural systems. The results confirm the potential of HPMCs as reliable materials for demanding engineering applications requiring superior wear resistance.